Improvement Of Habituation Methods In Learning Islamic Education At Mts Al-Jumhuriyah Sei Rattan - Ismail, Ismail; Tang, Muhammad; Firmansyah, Firmansyah (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Realizing a generation that is able to compete in the future, teachers as designers of education in the scope of change, should be able to design learning using models, strategies, methods and even learning media in every lesson. This type of research is classroom action research, this research uses the Kurt Lewin model, which is action research consisting of four main components, namely: planning, action, observation, and reflection. The subjects in this study were class VIII at MTs Al-Jumhuriyah Sei Rattan as many as 25 students. The data collection instrument used is an observation sheet. From the research carried out, it was concluded that the habituation method in Islamic Religious Education lessons for grade VIII students can increase. This improvement can be seen from the observation sheet given by the researcher. The result of the action in cycle 1 was an average of 38.74 and cycle II was an average of 84.7. Judging from the results of cycle I to cycle II, there is an increase that shows an increase in the learning outcomes of Islamic Religious Education. Thus the research hypothesis is acceptable.